Engaging with Women's Knowledge in Bristol Bay Fisheries through Oral History and Participatory Ethnography. Issue 7 (20th May 2019) - Lavoie, Anna; Lee, Jean; Sparks, Kim; Hoseth, Gayla; Wise, Sarah
Abstract : Research on women's contributions to Alaska's salmon fisheries is limited despite their historical engagement in commercial and subsistence fisheries. We interviewed women engaged in salmon fisheries in Bristol Bay, Alaska and illustrate how oral history and participatory ethnography methods contribute to voices being heard, that have been excluded from fisheries research and management. Four broad themes emerged from the interviews: women's knowledge and leadership; social cohesion; environmental change; and identity and place. Women assume major roles by contributing to the preservation of salmon fishing knowledge and cultural values through cross‐generational knowledge transfer. Their participation in fisheries, deep knowledge of local resources, and education of youth of the cultural value of fishing and the environment are critical to community socio‐cultural and economic wellbeing. We conclude that women's knowledge may be critical in fisheries management decisions, community resilience, and socio‐ecological sustainability in a region facing increased threats from climate change.